2012
DOI: 10.3174/ajnr.a3357
|View full text |Cite
|
Sign up to set email alerts
|

Recanalization with Stent-Retriever Devices in Patients with Wake-Up Stroke

Abstract: BACKGROUND AND PURPOSE: Stent-retriever devices play an increasing role in the interventional treatment of acute stroke patients, because fast recanalization can be achieved. The purpose of this study was to evaluate the feasibility of stent-retriever recanalization in patients with wake-up stroke in the anterior circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…34,36 For both case series, overall results are not compelling with high mortality (23% and 37%) and high rates of symptomatic intracranial hemorrhage (14% and 21%) for both studies, while with regard to good outcome (mRS, 0-2 at day 90), the results were different with 48% 34 in one case series and only 11% in the other case series. 36 The majority of reports do not provide information on the timing of interventions.…”
Section: September 2015mentioning
confidence: 55%
See 2 more Smart Citations
“…34,36 For both case series, overall results are not compelling with high mortality (23% and 37%) and high rates of symptomatic intracranial hemorrhage (14% and 21%) for both studies, while with regard to good outcome (mRS, 0-2 at day 90), the results were different with 48% 34 in one case series and only 11% in the other case series. 36 The majority of reports do not provide information on the timing of interventions.…”
Section: September 2015mentioning
confidence: 55%
“…34,36 For both case series, overall results are not compelling with high mortality (23% and 37%) and high rates of symptomatic intracranial hemorrhage (14% and 21%) for both studies, while with regard to good outcome (mRS, 0-2 at day 90), the results were different with 48% 34 in one case series and only 11% in the other case series. 36 The majority of reports do not provide information on the timing of interventions. In 1 study, median door to needle time for intravenous thrombolysis that was performed before intraarterial treatment was 154 minutes, which was significantly longer than in a comparison group of patients with known onset stroke screened by the same imaging approach (94 minutes).…”
Section: September 2015mentioning
confidence: 55%
See 1 more Smart Citation
“…Recently, several trials emphasized the importance of patient selection for reperfusion therapy, with the tissue clock shown by multiparametric MR imaging techniques. [6][7][8][9]12 We selected, in our study, patients using DWI/FLAIR mismatch and clinical-diffusion mismatch among MR imaging criteria. As reported by Thomalla et al, 3 a patient with an acute ischemic lesion detected with DWI but not with FLAIR imaging is likely to be within 4.5 hours of symptom onset with high specificity (78%; 95% CI, 72%-84%) and high positive predict value (83%; 95% CI, 79%-88%).…”
Section: Predictive Factors Associated With Favorable Outcome At Day mentioning
confidence: 99%
“…[4][5][6][7][8][9] Only a few reports have evaluated the feasibility of endovascular therapies in patients with wake-up stroke. [10][11][12] Recently, randomized studies have demonstrated that mechanical thrombectomy is an alternative and synergistic method of treatment to IVT in acute ischemic stroke, with a higher recanalization rate (66%-100%) and a more favorable outcome (32.6%-71%). [13][14][15][16][17] The aim of this study was to describe the experience of our center with 41 patients presenting with a stroke of an unknown time of symptom onset in the anterior circulation, who were treated by using a coalescent stroke-management protocol with IVT, mechanical thrombectomy, or bridging therapy based on DWI/FLAIR mismatch.…”
mentioning
confidence: 99%